Estimates of total neuron number show that neonatal ethanol causes immediate and lasting neuron loss in cortical and subcortical areas - Smiley, John F.; Bleiwas, Cynthia; Marino, Brandon M.; Vaddi, Prerana; Canals-Baker, Stefanie; Wilson, Donald A.; Saito, Mariko (Frontiers in Neuroscience, 2023)
In neonatal brain development there is a period of normal apoptotic cell death that regulates adult neuron number. At approximately the same period, ethanol exposure can cause a dramatic spike in apoptotic cell death. While ethanol-induced apoptosis has been shown to reduce adult neuron number, questions remain about the regional selectivity of the ethanol effect, and whether the brain might have some capacity to overcome the initial neuron loss. The present study used stereological cell counting to compare cumulative neuron loss 8 h after postnatal day 7 (P7) ethanol treatment to that of animals left to mature to adulthood (P70). Across several brain regions we found that the reduction of total neuron number after 8 h was as large as that of adult animals. Comparison between regions revealed that some areas are more vulnerable, with neuron loss in the anterior thalamic nuclei > the medial septum/vertical diagonal band, dorsal subiculum, and dorsal lateral geniculate nucleus > the mammillary bodies and cingulate cortex > whole neocortex. In contrast to estimates of total neuron number, estimates of apoptotic cell number in Nissl-stained sections at 8 h after ethanol treatment provided a less reliable predictor of adult neuron loss. The findings show that ethanol-induced neonatal apoptosis often causes immediate neuron deficits that persist in adulthood, and furthermore suggests that the brain may have limited capacity to compensate for ethanol-induced neuron loss.